The effect of bladder sensation on uroflowmetry parameters in healthy young men. Issue 5 (7th April 2015) - Kaynar, Mehmet; Kucur, Mustafa; Kiliç, Ozcan; Akand, Murat; Gul, Murat; Goktas, Serdar
Abstract : Aims: To investigate the effect of the bladder sensation grade on uroflowmetry parameters. Methods: Fifty healthy volunteering young men were enrolled in the present study. In total, three uroflowmetry evaluations were made. Qmax, Qave, VV, and PVR urine was obtained three times in three described bladder sensation grades, nearly at the same time of the day. Results: The mean age of the participants in the present study is 29.08 ± 3.8 years. The mean Qmax values of the volunteers were 17.4 ± 4.8 ml/s, 24.1 ± 6.0 ml/s, and 29.6 ± 6.5 ml/s in the first, second, and third, voiding desire grades, respectively. The mean Qave values were 9.9 ± 2.1 ml/s, 12.9 ± 2.9 ml/s, and 15.9 ± 4.0 ml/s for each of the voiding desire grades mentioned. A statistically significant difference was obvious for all three bladder sensation grades in terms of Qmax and Qave values ( P = 0.000). However, no statistically significant difference was seen regarding the PVR urine volumes. The mean voided volume in the first, second and third uroflowmetry were 140 ± 42 ml, 245 ± 64 ml, and 449 ± 105 ml, respectively. The highest Qmax and Qave values were obtained when the desire to void was urgent. Conclusions: The findings of the study show that, uroflowmetry evaluations are to be made if the patients have a strong desire to void. Only thus the highest Qmax values can be obtained; yet, the degree of perceived bladder sensation does not have a statistically significant impact on PVR quantity. Neurourol. Urodynam. 35:622–624, 2016 . © 2015 Wiley Periodicals, Inc.